Navigating Sexualization by Clients: Critical and Clinical Perspectives - Ellen Smith (Affilia, 2026)
A challenging aspect of practice for social work students is the client's expression of sexual feelings for them. From a feminist perspective, sexualization by clients may be seen as an expression of gendered power dynamics. Historically, the emergence of sexual feelings on the part of the client has been conceptualized as erotic transference. This article presents a conceptual framework to help students explore the range of potential meanings of sexualization by clients. It highlights the power dynamics that can play out between clients and social workers, including those related to intersectional social identities, trauma history, and role in the relationship.